GEOSPATIAL DATA QUALITY OF THE SERVIR CORS NETWORK - J. Santos; R. Teodoro; N. Mira; V. B. Mendes (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
The SERVIR Continuous Operation Reference Stations (CORS) network was implemented in 2006 to facilitate land surveying with Global Navigation Satellite Systems (GNSS) positioning techniques. Nowadays, the network covers all Portuguese mainland. The SERVIR data is provided to many users, such as surveyors, universities (for education and research purposes) and companies that deal with geographic information. By middle 2012, there was a significant change in the network accessing paradigm, the most important of all being the increase in the responsibility of managing the network to guarantee a permanent availability and the highest quality of the geospatial data. In addition, the software that is used to manage the network and to compute the differential corrections was replaced by a new software package. These facts were decisive to perform the quality control of the SERVIR network and evaluate positional accuracy. In order to perform such quality control, a significant number of geodetic monuments spread throughout the country were chosen. Some of these monuments are located in the worst location regarding the network geometry in order to evaluate the accuracy of positions for the worst case scenarios. Data collection was carried out using different GNSS positioning modes and were compared against the benchmark positions that were determined using data acquired in static mode in 3-hour sessions. We conclude the geospatial data calculated and provided to the users community by the network is, within the surveying purposes, accurate, precise and fits the needs of those users.